ANALYSIS OF THE IMPACT OF SPORTS REGULATIONS ON ACHIEVING GOALS AND SUCCESS IN COMPETITIONS - Mohammed Rashid Mohammed (Proximus Journal Publishing, 2024)
The outdoor sports activity is one of the duties of university sports and its objectives that it works for, so a large percentage of students participate in this activity who find an outlet for them, sports activity includes many benefits and educational values that in turn help achieve the goals of the general program of the university, such as training on leadership, cooperation, emotional maturity, self-reliance and responsibility, hence the importance of research because of the many benefits of sports activity for students and to contribute to identifying the obstacles that University sports is one of the paragraphs of the correct scientific program for any university, which takes into account when developing the most important ways and methods attributed to the transition of the student from the stage of formal system and training of mental faculties
Keywords: Organization; Athletic; Achievement; Goals; Competitions